Classic Ulcerative Pyoderma Gangrenosum Is a T Cell-Mediated Disease Targeting Follicular Adnexal Structures: A Hypothesis Based on Molecular and Clinicopathologic Studies - Wang, Elizabeth A.; Steel, Andrea; Luxardi, Guillaume; Mitra, Anupam; Patel, Forum; Cheng, Michelle Y.; Wilken, Reason; Kao, Jason; de Ga, Kristopher; Sultani, Hawa; Merleev, Alexander A.; Marusina, Alina I.; et al. (Frontiers in Immunology, 2018)
Background: Pyoderma gangrenosum (PG) is a debilitating ulcerative skin disease that is one of the most common associated diseases seen in patients with inflammatory bowel disease and rheumatoid arthritis. Although PG is classified as a neutrophilic dermatosis, its pathophysiology is poorly understood. Objective: Use data obtained from patient reported histories, immunohistochemistry, and gene expression analysis to formulate a hypothesis on PG pathophysiology. Methods: Ten PG patients participated and answered questions about new ulcer formation. Skin biopsies of healed prior ulcers and adjacent normal skin were obtained from four patients for immunohistochemistry. Scars from healthy patients and patients with discoid lupus were used as additional controls. New onset PG papules were analyzed using immunohistochemistry and gene expression analysis via qRT-PCR. Results: All PG patients reported that healed sites of previous ulceration are refractory to re-ulceration. Simultaneous biopsies of healed and uninvolved skin triggered ulceration only in the latter. On immunohistochemistry, healed PG scars showed complete loss of pilosebaceous units, which were present in normal skin, and to a lesser extent in control scars, and discoid scars. Early PG papules showed perivascular and peripilosebacceous T cell infiltrates, rather than neutrophils. These early inflammatory events were dominated by increased gene expression of CXCL9, CXCL10, CXCL11, IL-8, IL-17, IFNG, and IL-36G; and transcription factors consistent with Th1 phenotype. Limitations: Small sample size was the main limitation. Conclusion: We put forth the hypothesis that PG is a T cell response resulting in the destruction of pilosebaceous units.